The effect of combined treatment with niacin and chromium (III) chloride on the different tissues of hyperlipemic rats - Atac, Inci A.; Peksel, Aysegul; Yanardag, Refiye; Sokmen, Bahar B.; Doger, Mutluhan M.; Bilen, Zeynep G. (TAYLOR & FRANCIS LTD, 2006)
We investigated the effects of a combined treatment with chromium (Cr) and niacin on the spleen, tongue, and lens tissues in terms of lipid peroxidation (LPO), glutathione (GSH), serum catalase (CAT), lactate dehydrogenase (LDH), serum cholesterol, and total lipid levels in normal and hyperlipemic rats. In this study, female 1-year-old Swiss albino rats were used. The rats were randomly divided into four groups. Group I rats (control) were fed with standard pellet chow. Group II rats were fed a lipogenic diet in which 2% cholesterol, 0.5% cholic acid, and 20% sunflower oil were added and were given 3% alcoholic water for 60 days. Group III rats were fed with the same lipogenic diet and were treated with a dose of 250 mu g/kg body weight CrCI3 center dot 6H(2)O and 100 mg/kg body weight niacin, for 45 days, by gavage. The rats in group IV were fed with pellet chow and treated with 250 mu g/kg body weight CrCI3 center dot 6H(2)O and 100 mg/kg body weight niacin, by gavage, for 45 days. After 2 weeks, the animals showed symptoms of hyperlipemia. On the 60th day, tissue and blood samples were taken. We have observed decreased CAT activity and GSH levels, increased LDH activity, cholesterol, total lipid, and LPO levels in hyperlipemic rats. Niacin and Cr administration to hyperlipemic rats increased tissue GSH levels and CAT activity and decreased tissue LPO levels and LDH activity, cholesterol, and total lipid levels compared with hyperlipemic rats. We conclude that the administration of a combination of niacin and chromium has a protective effect against oxidative damage to tongue, lens, and spleen tissues as a result of hyperlipemia.
Keywords: chromium; glutathione; hyperlipemia; lipid peroxidation; niacin; tissues; NICOTINIC-ACID COMPLEX; LIPID-PEROXIDATION; CARDIOVASCULAR-DISEASE; OXIDATIVE STRESS; FREE-RADICALS; DIETARY CHROMIUM; AQUEOUS EXTRACT; RISK-FACTORS; CHOLESTEROL; SUPPLEMENTATION; Chemistry; Pharmacology & Pharmacy; Toxicology